2022
DOI: 10.1101/2022.04.27.489663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compensatory traits can explain concave cost function of purely sexual traits

Abstract: The cost of ornamentation is often measured experimentally to study the relative importance of sexual and viability selection for ornamentation, but these experiments can lead to a misleading conclusion when compensatory trait is ignored. A famous, classic experiment on the outermost tail feathers in the barn swallow Hirundo rustica, explains that the U-shaped aerodynamic performance of the outermost tail feathers would be the evolutionary outcome mainly through viability selection for optimal tail length, but… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
5
1
Order By: Relevance
“…In support of these theories, when experimentally manipulating outermost tail feathers in the barn swallow, Evans and colleagues found that estimated peak aerodynamic performance located only around 10 mm shorter from the current outermost tail feathers, suggesting that most forked tails evolved through viability selection for aerodynamic function (e.g., Evans 1998; Buchanan & Evans 2000; Rowe et al 2001). However, their studies, like those of many others that manipulated ornaments, did not take into account the presence of compensatory traits (Hasegawa 2023; also see Oufiero & Garland 2007; Husak & Swallow 2011 for general cautions of ignoring compensatory traits). According to Norberg (1994, p.231), any experimental shortening and lengthening of the outer tail feathers is likely to upset an original co-adapted character set.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…In support of these theories, when experimentally manipulating outermost tail feathers in the barn swallow, Evans and colleagues found that estimated peak aerodynamic performance located only around 10 mm shorter from the current outermost tail feathers, suggesting that most forked tails evolved through viability selection for aerodynamic function (e.g., Evans 1998; Buchanan & Evans 2000; Rowe et al 2001). However, their studies, like those of many others that manipulated ornaments, did not take into account the presence of compensatory traits (Hasegawa 2023; also see Oufiero & Garland 2007; Husak & Swallow 2011 for general cautions of ignoring compensatory traits). According to Norberg (1994, p.231), any experimental shortening and lengthening of the outer tail feathers is likely to upset an original co-adapted character set.…”
Section: Figmentioning
confidence: 99%
“…Dotted line is shown as a ridge line. See Hasegawa (2023) for detailed explanation. Illustration was given by Hasegawa (2023).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because, when tail length is manipulated, aerodynamic ability is impaired because of the reduction in functional integrity associated with compensatory traits (Norberg, 1994, p 231; see fig. 3 in Hasegawa, 2022). Macroevolutionary analysis, i.e., an alternative approach focusing on the evolution of focal traits, provided insight into the evolution of female tail length.…”
Section: Introductionmentioning
confidence: 99%
“…The barn swallow Hirundo rustica is a socially monogamous bird and model species of sexual selection, in which females have been shown to behaviorally prefer tail-elongated males, explaining their long outermost tail feathers. For example, experimental manipulation of tail length affects acceptance/rejection of extra-pair copulation (Møller, 1988;reviewed in Møller, 1994;Romano et al, 2017;Turner, 2006), which is further reinforced by comparative evidence of the evolution of tail fork depth in relation to opportunities for extrapair paternity in hirundines or the family Hirundinidae (Hasegawa & Arai, 2020a, 2022. Female barn swallows have shorter tails than males, but some studies suggest that female tails are nonetheless costly to produce and maintain (e.g., Cuervo et al, 2003;Cuervo & de Ayala, 2014;Hasegawa et al, 2020;Rowe et al, 2001).…”
mentioning
confidence: 99%